A ciência na cibercultura: o discurso híbrido da divulgação científica na era da comunicação virtual - Rosa, Caroline Petian Pimenta Bono (2014)
This research examines the hypermedia discourse of science in blogs. The focus is on the dissemination of Brazilian studies of major knowledge areas established by CNPq. The object of study consists of the types of discourse in the contents delivered in cyberspace by means of hypermedia navigation. An analysis is made of the operationality of cyberculture resources in science communications disseminated through blogs. The corpus of this analysis comprises the blogs of the Scientific Blog Ring portals of Science Blogs Brazil, known as Research Blogging. The analysis involves postings between 2009 and 2013. The methods of observation and data collection used in the project are based on a qualitative methodology that includes the theoretical foundations of Discourse Analysis. In-depth interviews are also conducted with a group of bloggers and blog readers to analyze the production of and response to the scientific information. The research problem can be formulated as follows: With what discourses is science built in virtual newspapers and how do hypermedia resources make up the science disseminated to society? Faced with this problem, we put forward the following hypotheses: (1) the discourse disseminated through virtual newspapers translates de facto science to a possibly layperson audience that seeks information about the subject; (2) depending on how the discourse articulated between text and hypermedia resources is interpreted, it can hamper the approximation between the reader and science; (3) albeit on virtual sites with informal content, what is published is aimed at the bloggers own science peers rather than a wider public. The theoretical rationale includes the foundations of social dromology, media exposure, cybercultural dromocracy and glocal studies. The results indicate that the science circulating in virtual newspapers consists primarily of the discourse of science dissemination for audiences that are sometimes peers and at other times interested laypeople. The predominating discourse is informative and descriptive, democratizing the published information, with the discourse built for the expansion of science, consisting of text, image and sound, which results in a hybrid discourse